Detection of children with bronchopulmonary pathology and risk of its forming using the «EDIFAR» computer system - T. V. Zabolotskikh; Yu. L. Mizernitsky; L. A. Dartau (Бюллетень сибирской медицины)
In the article it has been shown the efficiency of children detection with bronchopulmonary pathology and risk of its forming using the «EDIFAR» computer system. Screening with this computer technology allows in short terms a pictorial view of children’s health on the primary health service territory. This investigation has been made in pediatric polyclinic ‹ 4 in Blagoveshchensk. The results show the actual prevalence of respiratory diseases at children aged 0—7 years and are an evidence of a significant exceeding of disease indices as compared to the official statistic data. Information get with the computer system is necessary not only for address aid but is useful in conditions of insurance medicine and market principles of funds spending for health protection as well.